Range Of Motion (ROM) Exercise dengan Frekuensi 1 Kali Per 3 Hari Dapat Meningkatkan Rentang Gerak Sendi Lutut pada Lansia dengan Gangguan Mobilitas Fisik - Muzdaliah, Ika; husaeni, hermin; Muzakkir, Muzakkir; Mutmainna, Amriati; Wijayaningsih, Kartika Sari (Journal of Telenursing (JOTING), 2025)
Joint flexibility decreases in the elderly due to degenerative processes in the joints, connective tissue, and cartilage. This is also caused by a reduction in the elasticity of muscle fibers, where the connective tissue in muscle fibers increases. This study aims to examine the effect of Range of Motion (ROM) exercises with a frequency of once every 3 days on improving knee joint Range of Motion in elderly individuals with physical mobility disorders. The method used is quantitative with a pre-post experimental design using a One-group pre-post test design approach. The research sample was selected using purposive sampling, with a total of 20 elderly respondents. The study was conducted in three therapy sessions on days 1, 4, and 8. The results showed a significant difference in the extension and flexion angles of the knee joint before and after the ROM therapy. The p-value obtained for both the knee extension and flexion angles was 0.000 < 0.05, indicating a significant improvement in knee joint flexibility after performing ROM exercises. In conclusion, ROM exercises performed with a frequency of once every 3 days are effective in improving knee joint Range of Motion in elderly individuals with physical mobility disorders. Therefore, this exercise is recommended as a routine intervention for the elderly at least twice a week to maintain joint flexibility and reduce the risk of mobility disorders. Keywords: Elderly, Range of Motion, Knee Joint